(untitled) (Marketing Journal, 2025)
This article explores the theoretical foundations and methodological approaches to evaluating the efficiency of fixed asset utilization in railway transport enterprises. The study examines the system of indicators for assessing asset efficiency, including modern methods used in international practice such as Data Envelopment Analysis (DEA), as well as indicators like capital return, capital intensity, and capital -labor ratio. Based on the case of Uzbekistan’s railway transport companies, the article identif ies key directions for improving the effectiveness of fixed asset usage.